PENGARUH FAKTOR-FAKTOR PENENTU PROGRAM K3 TERHADAP KINERJA KARYAWAN DI PERUM JASA TIRTA II - Harahap, Iskandara Junaidi; Darlius (Jurnal Satya Mandiri Manajemen dan Bisnis, 2017)
In a competitive business world, safety management should be managed like managing other aspects of activities, such as production, marketing, finance and human resources. Employee performance is not only influenced by motivation, work culture, job satisfaction, but it can be influenced to what extent the company's K3 program can work. This research aims to explain the influence of determinants of K3 program on Perum Jasa Tirta II employees' performance. The research method is used explanatory research method, using questionnaires as a data gathering tool distributed to 80 employees of PLTA Business Unit in Perum Jasa Tirta II West Java. The results of this research indicate the determinants of K3 program consist of safety leadership (X1), safety training (X2) , safety procedure (X3), safety communication (X4), work involvement (X5), compensation (X6) and safety equipment (X7), positively affects the performance variable (Y) the employees of PLTA Business Unit in Perum Jasa Tirta II with determination adjusted koefisien is 24,7 % and value FCount (4,695) > Ftable (2,61)